COVID - 19: A Reflection (Janaki Medical College Journal of Medical Science, 2020)
Corona virus disease-19 has caused widespread morbidity and mortality and significant economic disruption. Most individuals including me did not expect the pandemic to affect human life for so long. There have been multiple waves in some countries. In most persons the disease is mild and these individuals can spread the virus. About 15% of those infected may need hospital treatment and intensive care. Traditional measures like lockdowns, travel restrictions and quarantine have been used in the absence of an effective treatment or vaccine. A climate of fear has been created by some studies and media reports. Traditional daily activities have been affected and some may no longer be possible. Schools and colleges have shut down and shifting education online. There have been organizational failures and instances of profiteering during the pandemic. Many of the measures implemented have required individuals to provide personal data and accept restrictions on their freedom. The tourism and travel industry has been hit hard and millions of individuals may slip back into poverty. The information about the pandemic is rapidly evolving and is often confusing.